ZONA PERI-URBAN SEMARANG METROPOLITAN: PERKEMBANGAN DAN TIPOLOGI SOSIAL EKONOMI - Iwan Rudiarto; Wiwandari Handayani; Bitta Pigawati; P Pangi (TATALOKA, 2013)
Peri-urban can be understood as an area mostly rural located in the surrounding urban center which also has obvious urban character. This paper aims to assess the socio-economic development of Peri-Urban Areas (PUA) of the Metropolitan Semarang in 1990-2011. Study area covers 295 villages that are included in the delineation of the Metropolitan area of Semarang. They are distributed in four cities/districts, i.e.: Semarang city, Semarang regency, Kendal regency, and Demak regency. Satellite imaginary analysis and Geographic Information System (GIS) analysis including overlay analysis, buffer and distance analysis, and descriptive spatial analysis were applied for the analysis. The analysis results show that the PUA of metropolitan Semarang has undergone changes and shifts in socio-economic conditions of rural significant to urban areas. In conclusion, the existence of PUA has led to the blurring of the distinction between rural and urban areas which are not simply dichotomized. Integrated development policies are very essential for more balanced urban development in Semarang Metropolitan region.